Pengembangan Video Gerak dan Lagu Anti Bullying Untuk Siswa Sekolah Dasar - Nadia Kurnia Sari; Andika Gutama; Cicilia Ika Rahayu Nita (LPPM STIKI Malang, 2025)
Bullying in schools is currently a serious concern for the education and health services because bullying cases are increasingly widespread, especially in the school environment. Without bullying incidents, learning activities at school become enjoyable, so alternative solutions are needed to minimize bullying cases that occur in elementary schools. This research aims to describe the process, feasibility and practicality of developing anti-bullying movement videos and songs. This research uses a development research method with a 4D model consisting of Define, Design, Develop, Dessiminat. The data used in this research are qualitative data and quantitative data. The results of the feasibility test for the Anti-Bullying Movement Video and Song met the